1976
DOI: 10.1017/s0021859600061141
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorus requirement of pregnant sheep

Abstract: Thirty-eight mature Scottish Blackface sheep were mated at pasture and 32 brought indoors when 3-4 weeks pregnant. Eight were killed at this stage as controls (CI). The remaining 24 were offered a basal hay ration (200 g/head/day) supplemented with a semi-purified diet containing 84 g crude protein/kg and either 1-5 (Px), 2-8 (P 2 ) or 9-3 (P 3 ) g P/kg dry matter. The rate of feeding of the supplement allowed a mean daily P intake (g/day) in groups P x , P 2 and P 3 of 1-1, 1-6 and 4-7 and 1-6, 2-5 and 7-9 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…If this assumption is correct, then endogenous faecal loss of P should remain at this low level, irrespective of P intake, providing animals are fed just enough P to meet their requirements. Although low endogenous faecal losses of P have been observed in sheep given semi-purified diets deficient in P (Sykes & Dingwall, 1976) or very poor natural diets (Field, Sykes & Gunn, 1974) and there is some evidence that the high endogenous faecal loss associated with high P intakes can be reduced in response to an increased P demand (present study; Braithwaite, 19836) or an infusion of Ca into the blood (Braithwaite, 1984), there is yet no firm evidence that the endogenous loss in animals fed according to requirements can be kept constant at this low level. Rather, it seems more likely that the inevitable endogenous faecal loss, and hence maintenance requirement, must increase to some extent with increased P intake.…”
Section: Resultsmentioning
confidence: 99%
“…If this assumption is correct, then endogenous faecal loss of P should remain at this low level, irrespective of P intake, providing animals are fed just enough P to meet their requirements. Although low endogenous faecal losses of P have been observed in sheep given semi-purified diets deficient in P (Sykes & Dingwall, 1976) or very poor natural diets (Field, Sykes & Gunn, 1974) and there is some evidence that the high endogenous faecal loss associated with high P intakes can be reduced in response to an increased P demand (present study; Braithwaite, 19836) or an infusion of Ca into the blood (Braithwaite, 1984), there is yet no firm evidence that the endogenous loss in animals fed according to requirements can be kept constant at this low level. Rather, it seems more likely that the inevitable endogenous faecal loss, and hence maintenance requirement, must increase to some extent with increased P intake.…”
Section: Resultsmentioning
confidence: 99%
“…Digestibility SYKES and COOP (1976) found in continuous infections of lambs with Trichostrongvltrs coltrbrifrmis, a small intestinal parasite, n o reduction in digestibility. The same authors (SYKES and COOP 1977) found a depressed protein digestibility in lambs continuously infected with Ostertagia circumcincta, an abomasal parasite. This was found in comparison to pair fed animals.…”
Section: Discussionmentioning
confidence: 79%
“…Reduced performance may be due to a lowered digestive efficiency of the parasitized gastro-intestinal tract, resulting in lower apparent digestibility o f the ration as found by BREMNER (1961) and SYKES and COOP (1977). However, in other studies such a change in digestibility was not observed (SYKES and COOP 1976;ROSEBY 1977;POPPI et al 1981). Absorbed nutrients may be used less efficiently by infected animals.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The non-lactating cows were used in only one trial (4 animals) for the study of the relationship between phosphorus and calcium absorption and their concentration in the diet [28]. The only pregnant animals of our database were ewes used in 4 trials (64 animals) and weighing 46 kg [29], 50 kg [26], 65 kg [30], and 70 kg [27]. The lactating ewes ingested 859 g DM and weighed on average 59.6 kg.…”
Section: General Resultsmentioning
confidence: 99%